Click chemistry based synthesis of dopamine D4 selective receptor ligands for the selection of potential PET tracers - Banerjee, Ashutosh; Maschauer, Simone; Hübner, Harald; Gmeiner, Peter; Prante, Olaf (Bioorganic & Medicinal Chemistry Letters, 2013)
Taking advantage of click chemistry, a library of N-arylpiperazinylmethyl triazoles bearing fluoro substituted appendages was synthesized and the target compounds were investigated for dopamine and serotonin receptor binding. With the aim to bias their hydrophilicity and to optimize their D4 receptor affinity and selectivity, a concise series of triazoles containing fluoroalkyl, fluoroalkoxy, fluoroalkoxyphenyl, and deoxyfluoroglucosyl substituents was studied. The D4 receptor affinity and selectivity could be tuned by altering the chemical moiety attached to the triazole unit. Among the test compounds, the fluoroethoxyphenyl derivative 15b showed weak partial agonism at D4 and a K value of 14 nM, while its fluoropropoxyphenyl homologue 16a turned out to act as a neutral D4 antagonist (K = 5.1 nM). Both, 15b and 16a revealed an excellent balance between D4 receptor affinity and subtype selectivity, providing lead candidates for the development of F-labeled radioligands for D4 receptor imaging studies by positron emission tomography (PET). © 2013 Elsevier Ltd. All rights reserved.

Development of Covalent Ligand-Receptor Pairs to Study the Binding Properties of Nonpeptidic Neurotensin Receptor 1 Antagonists. - Kling, Ralf; Plomer, Manuel; Lang, Christopher; Banerjee, Ashutosh; Hübner, Harald; Gmeiner, Peter (ACS Chemical Biology, 2016)
The neurotensin receptor NTS1 has been suggested to be of pharmaceutical relevance, as it was found to exert modulatory effects on dopaminergic signal transduction and to be involved in tumor progression. Rational drug design of NTS1 receptor ligands requires molecular insights into the binding behavior of a particular lead compound. Although crystal structures of NTS1 have revealed the molecular determinants of peptide-agonist interactions, the binding mode of small-molecule antagonists remains largely unknown. Employing a disulfide-based tethering approach, we developed covalently binding molecular probes. The ligands 1 and 2 are based on the pharmacophore of the nonpeptidic NTS1 antagonist SR142948A, allowing the formation of a disulfide bond to an engineered cysteine residue of NTS1. The position of the covalent bond between Cys127(2.65) and the ligand was used to predict the binding mode of the covalent antagonist 1 and its parent compound SR142948A by molecular dynamics simulations.

Discovery of G Protein-Biased Dopaminergics with a Pyrazolo[1,5-a]pyridine Substructure - Möller, Dorothee; Banerjee, Ashutosh; Uzuneser, Taygun; Skultety, Marika; Huth, Tobias; Plouffe, Bianca; Hübner, Harald; Alzheimer, Christian; Friedland, Kristina; Müller, Christian P.; Bouvier, Michel; Gmeiner, Peter (Journal of Medicinal Chemistry, 2017)
1,4-Disubstituted aromatic piperazines are privileged structural motifs recognized by aminergic G protein-coupled receptors. Connection of a lipophilic moiety to the arylpiperazine core by an appropriate linker represents a promising concept to increase binding affinity and to fine-tune functional properties. In particular, incorporation of a pyrazolo[1,5-a]pyridine heterocyclic appendage led to a series of high-affinity dopamine receptor partial agonists. Comprehensive pharmacological characterization involving BRET biosensors, binding studies, electrophysiology, and complementation-based assays revealed compounds favoring activation of G proteins (preferably G(o)) over beta-arrestin recruitment at dopamine D-2 receptors. The feasibility to design G protein-biased partial agonists as putative novel therapeutics was demonstrated for the representative 2-methoxyphenylpiperazine 16c, which unequivocally displayed antipsychotic activity in vivo. Moreover, combination of the pyrazolo[1,5-a]pyridine appendage with a 5-hydroxy-N-propy1-2-aminotetraline unit led to balanced or G protein-biased dopaminergic ligands depending on the stereochemistry of the headgroup, illustrating the complex structure functional selectivity relationships at dopamine D2 receptors.

Molecular Determinants of Biased Agonism at the Dopamine D2 Receptor - Weichert, Dietmar; Banerjee, Ashutosh; Hiller, Christine; Kling, Ralf; Hübner, Harald; Gmeiner, Peter (Journal of Medicinal Chemistry, 2015)
UnivIS-Import:2015-03-11:Pub.2015.nat.dchph.lphch.molecu

Structure-guided development of selective M3 muscarinic acetylcholine receptor antagonists - Liu, Hongtao; Hofmann, Josefa; Fish, Inbar; Schaake, Benjamin; Eitel, Katrin; Bartuschat, Amelie; Kaindl, Jonas; Rampp, Hannelore; Banerjee, Ashutosh; Hübner, Harald; Clark, Mary J.; Vincent, Sandra G.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Keywords: Muscarinic receptor; Subtype selectivity; G protein-coupled receptor; Drug design; Crystal structure

Structure-odor relationships of linalool, linalyl acetate and their corresponding oxygenated derivatives - Elsharif, Shaimaa; Banerjee, Ashutosh; Büttner, Andrea (Frontiers in Chemistry, 2015)
Linalool 1 is an odorant that is commonly perceived as having a pleasant odor, but is also known to elicit physiological effects such as inducing calmness and enhancing sleep. However, no comprehensive studies are at hand to show which structural features are responsible for these prominent effects. Therefore, a total of six oxygenated derivatives were synthesized from both 1 and linalyl acetate 2, and were tested for their odor qualities and relative odor thresholds (OTs) in air. Linalool was found to be the most potent odorant among the investigated compounds, with an average OT of 3.2 ng/L, while the 8-hydroxylinalool derivative was the least odorous compound with an OT of 160 ng/L; 8-carboxylinalool was found to be odorless. The odorant 8-oxolinalyl acetate, which has very similar odor properties to linalool, was the most potent odorant besides linalool, exhibiting an OT of 5.9 ng/L. By comparison, 8-carboxylinalyl acetate had a similar OT (6.1 ng/L) as its corresponding 8-oxo derivative but exhibited divergent odor properties (fatty, greasy, musty). Overall, oxygenation on carbon 8 had a substantial effect on the aroma profiles of structural derivatives of linalool and linalyl acetat
Keywords: Linalool; linalyl acetate; gas chromatography-olfactometry; odor threshold in air; 8-oxolinalyl acetate; 8-carboxylinalyl acetate; odor qualities; retention index

Visualization and ligand-induced modulation of dopamine receptor dimerization at the single molecule level - Tabor, Alina; Weisenburger, S; Banerjee, Ashutosh; Purkayastha, Nirupam; Kaindl, Jonas; Hübner, Harald; Wei, Luxi; Groemer, Teja W.; Kornhuber, Johannes; Tschammer, Nuska; Birdsall, Nigel J.M.; Mashanov, Gregory I.; et al. (Scientific Reports, 2016)
G protein-coupled receptors (GPCRs), including dopamine receptors, represent a group of important pharmacological targets. An increased formation of dopamine receptor D-2 homodimers has been suggested to be associated with the pathophysiology of schizophrenia. Selective labeling and ligand-induced modulation of dimerization may therefore allow the investigation of the pathophysiological role of these dimers. Using TIRF microscopy at the single molecule level, transient formation of homodimers of dopamine receptors in the membrane of stably transfected CHO cells has been observed. The equilibrium between dimers and monomers was modulated by the binding of ligands; whereas antagonists showed a ratio that was identical to that of unliganded receptors, agonist-bound D-2 receptor-ligand complexes resulted in an increase in dimerization. Addition of bivalent D-2 receptor ligands also resulted in a large increase in D2 receptor dimers. A physical interaction between the protomers was confirmed using high resolution cryogenic localization microscopy, with ca. 9 nm between the centers of mass.